Constraints in the Adoption of Stress Tolerant Rice Varieties (STRVs) in Odisha - Satpathy, Dr. Abhijeet; Satpathy, Dr. (Mrs.) Bineeta; Jayasingh, Debi Kalyan (Indian Journal of Extension Education, 2025)
The study investigated barriers to the adoption of stress-tolerant rice varieties (STRVs) among farmers in Odisha during 2024-2025. Data from 240 randomly selected farmers, collected via an ex-post facto design and analysed using Henry Garrett’s ranking technique. The analysis revealed key constraints across social, economic, managerial, technological, and organisational dimensions. Major barriers identified were low literacy, social marginalization, risk aversion, high input costs, limited financial literacy, weak post-adoption evaluation, insufficient STRV knowledge, inadequate demonstration trials, and poorly designed training programs. The results highlight the complex interplay of these obstacles and emphasise the need for comprehensive interventions—such as targeted literacy and capacity-building initiatives, improved financial support, adaptive extension services, and participatory demonstrations, all tailored to meet the needs of marginalized farmers to enhance STRV adoption in the countryside.